Design a millimeter : wave antenna - Pan, Zhe (Nanyang Technological University, 2020)
Millimeter-wave Antennal is currently widely using on different communication field and 5G technology is based on Millimeter-wave, it has advantages compared to 4G like faster signal transmitting speed, wider bandwidth and so on.In this project, Millimeter-wave Dipole Antennal is designed to simulate and get antennal performance. There are 4 phases to design Millimeter-wave Antennal, a 28GHz ideal Millimeter-wave Antennal is designed to have the performances, by adding a balun-circuit with coaxial cable to have its performances again and compare to the ideal case. Following by design a metal cavity and place Millimeter-wave antennal inside this cavity to check the performances at different depths. At the end of this project, the measurement of the Millimeter-wave Antennal simulation result will be verified.